Effects of Atypical Hydrogen Bonds and π-π Interactions on Nonlinear Optical Properties Dimers of Triangular Structures Based on Perylene, Naphthalene, and Pyromellitic Diimides - Wang, Li (Langmuir : the ACS journal of surfaces and colloids, 2023)
Nonlinear optical (NLO) materials have become important materials in the field of high-speed optical devices due to the changes in light absorption and refraction caused by the photoelectric field. Compounds tend to exist as aggregates rather than single molecules, so intermolecular interactions are crucial to the nature of aggregates. Therefore, to study the effects of intermolecular interactions on nonlinear optical properties, we use a dimer simplified model and adopt the methods of controlling variables, which are the different intermolecular interactions resulting from the different stacking patterns of dimers based on the same monomer structures (2PMDI-1NDI and 2NDI-1PDI). It is found that compared with dimers involving π-π interactions, dimers involving C-H···O interactions have shorter intermolecular distances, larger intermolecular interaction energies, and smaller highest occupied molecular orbital-lowest unoccupied molecular orbital (HOMO-LUMO) energy gaps. Moreover, the C-H···O interactions are more conducive to the intermolecular charge transfers and more beneficial for increasing the nonlinear optical response values of aggregates with respect to π-π interactions. This work provides an important basis for the influence of intermolecular interactions on nonlinear optical properties